The Role of Islamic Law, Constitution, and Culture in Democracy in the UAE and Indonesia - Taufiqurrohman, A.H. Asari; Muhtar, Mohamad Hidayat; Ahmad, Ahmad; Kasim, Nur Mohamad; Imran, Suwitno Yutye (Universitas Islam Negeri Jakarta, 2024)
The study explores how Islamic law and local culture influence democracy in the United Arab Emirates (UAE) and Indonesia and how each country's constitution facilitates the implementation of democracy based on Islamic principles. In the context of the UAE, Islamic law (sharia) is the primary source of law, while in Indonesia, Pancasila and the 1945 Constitution establish a more inclusive and pluralist legal framework, enabling the practice of Islamic law in a context that respects religious freedom. The research employs juridical legal research with historical, comparative, and Islamic legal approaches and will be analyzed with descriptive-analytical methods. The results showed the role of Islamic law, constitution, and culture in shaping democracy in the UAE and Indonesia through public policies and laws that accommodate the wider community's interests. With its sharia law and authoritarian constitution, the UAE shows a democracy different from Indonesia, which implements an inclusive democracy based on Pancasila and the 1945 Constitution. Cultural factors also play a role, with the UAE influenced by the monarchy and ruling family loyalties, while Indonesia is influenced by ethnic and cultural diversity. Implementing Islamic democracy requires transforming power, inclusive dialogue, and balancing Islamic values and universal democracy. Abstrak: Penelitian ini mengeksplorasi bagaimana hukum Islam dan budaya lokal mempengaruhi demokrasi di Uni Emirat Arab (UEA) dan Indonesia serta bagaimana konstitusi masing-masing negara memfasilitasi penerapan demokrasi berdasarkan prinsip-prinsip Islam. Dalam konteks UEA, hukum Islam (syariah) merupakan sumber hukum utama sedangkan di Indonesia, Pancasila dan UUD 1945 membentuk kerangka hukum yang lebih inklusif dan pluralis. Hal ini memungkinkan penerapan hukum Islam dalam konteks yang menghormati kebebasan beragama. Penelitian ini menggunakan penelitian hukum yuridis dengan pendekatan sejarah, komparatif, dan hukum Islam yang dianalisis dengan metode deskriptif-analitis. Temuan penelitian menunjukkan peran hukum Islam, konstitusi, dan budaya dalam membentuk demokrasi di UEA dan Indonesia melalui kebijakan publik dan undang-undang yang mengakomodasi kepentingan masyarakat luas. UEA dengan hukum syariah dan konstitusi otoriternya menunjukkan demokrasi yang berbeda dengan Indonesia yang menerapkan demokrasi inklusif berdasarkan Pancasila dan UUD 1945. Faktor budaya juga berperan, UEA dipengaruhi oleh monarki dan kesetiaan keluarga penguasa sedangkan Indonesia dipengaruhi oleh keragaman etnis dan budaya. Penerapan demokrasi Islam memerlukan transformasi kekuasaan, dialog inklusif, dan keseimbangan nilai-nilai Islam dan demokrasi universal.